2002
DOI: 10.1088/0953-8984/14/44/308
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of C60under high pressure

Abstract: The dielectric properties of C60 have been measured as functions of temperature and hydrostatic pressure in the ranges 80–370 K and 0–0.8 GPa. The results show sharp anomalies at the rotational transition above 260 K and large relaxation peaks associated with the rotational ‘glass transition’. From the measured frequencies of the loss peaks we calculate the energy barrier for molecular jumping between the ‘pentagon’ and ‘hexagon’ molecular orientations. The energy barrier increases by 13% GPa−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Relevant to these results are prior studies indicating that solid C 60 arrays rotate almost freely in a rotationally disordered high‐temperature, face‐centered cubic phase (above 260 K at atmospheric pressure). This motion is said to slow down and is transformed into a ratcheting or rocking motion in an orientation‐ordered simple cubic phase at low temperatures and high pressures . Su et al demonstrated a structural phase transition at 260 K as well as an anomaly at 90 K resulting from a glass transition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant to these results are prior studies indicating that solid C 60 arrays rotate almost freely in a rotationally disordered high‐temperature, face‐centered cubic phase (above 260 K at atmospheric pressure). This motion is said to slow down and is transformed into a ratcheting or rocking motion in an orientation‐ordered simple cubic phase at low temperatures and high pressures . Su et al demonstrated a structural phase transition at 260 K as well as an anomaly at 90 K resulting from a glass transition.…”
Section: Resultsmentioning
confidence: 99%
“…This motion is said to slow down and is transformed into a ratcheting or rocking motion in an orientation-ordered simple cubic phase at low temperatures and high pressures. [38][39][40] Su et al 38,39 demonstrated a structural phase transition at 260 K as well as an anomaly at 90 K resulting from a glass transition. Furthermore, these investigators observed a Debye-like relaxation in the dielectric response, e 0 and tan d versus f curves at three temperatures for C 60 (OH) 29 and Sc 3 N@C 80 (OH) 18 are provided in Figures 3 and 4, respectively.…”
Section: Resultsmentioning
confidence: 99%